Regional Institutions at the Doorstep of post 2020 Cohesion Policy – Status Report from Hungary - Balázs Simó; Tamás Gordos; Viktória Józsa (DETUROPE)
‘My Region, My Europe, Our Future’ (EC, 2017). This is the main message of the Seventh Report on Economic, Social and Territorial Cohesion. In the post 2020 period, the European Commission continues to focus on the compliance with challenges of the knowledge-based economy, and in parallel, stands for a strong territorial approach and increased synergy and coordination of the connected sectoral financial means and measures. The question is if Member States are ready to face the challenges that are specified in the report, such as digital revolution, globalisation, demographic change and social cohesion, economic convergence and climate change. In connection to this basic question, our paper aims to provide an overview about the evolution – rise and fall - of the Hungarian regional level (NUTS2) institutions with a strong emphasis on the state-of-the art, especially regarding administrative capacities. Desk research focused on the era between 1990-2015, while empirical research – in the form of a questionnaire – was conducted in 2017 and 2018 amongst former employees of the former regional development agencies. As there are no institutionalized actors at regional level in Hungary responsible for the implementation of Cohesion Policy any more – with the exception of Central Hungary, that is currently under re-formulation – we hypothesize that former(?) regional development professionals as individuals could play an important role in the preparations for the post-2020 financial period. In case they are involved…